The effect of phase matching factor on four wave mixing in optical communication systems: fuzzy and analytical analysis. (23rd March 2009) - Singh, Amarpal; Sharma, Ajay K.; Kamal, T.S.
In this paper, a modified analysis of Four Wave Mixing (FWM) by incorporating the third-order dispersion parameters is reported. With the help of a modified formula for FWM crosstalk, the effect of second- and third-order dispersion parameters at different input channel powers has been analysed. Under the combined effect of second- and third-order dispersion parameters, the crosstalk introduced by FWM is reduced. Further, we propose a fuzzy-based approach using Adaptive-Network-Based Fuzzy Inference System (ANFIS) to calculate FWM power by varying input channel powers at different intensity-dependent phase-matching factors, and observed that the results are very similar to analytical results.